Degree of conversion of resin composites light activated by halogen light and led analyzed by ultraviolet spectrometry - Sgarbi, Sandra C.; Pereira, Stella Kossatz; Martins, Juliana Maria Habith; Oliveira, Maria A. Cesar; Mazur, Rui Fernando (Archives of Oral Research, 2010)
Objectives: The aim of this study was to compare the degree of conversion of different shades ofa composite resin activated with two different light sources. Material and method: Composite resin(Charisma™), A2 and SL were photoactivated with a halogen lamp and a LED based system, at threedifferent light activation times (10, 20 and 40s). The degree of conversion was analyzed by ultravioletspectroscopy with variation in wavelength. The data were submitted to ANOVA and the Games Howelltest (5%). Results: The resin composite shade SL presented a higher degree of conversion in depth thanthe resin composite shade A2. The three light activation times had no infl uence on the degree of conversionin the groups of resin composite SL light activated with halogen light and LED. Conclusion: It wasconcluded that the resin composite SL presented the highest degree of conversion, irrespective of thelight polymerization time and the light source used.